2015
DOI: 10.1371/journal.pone.0136375
|View full text |Cite|
|
Sign up to set email alerts
|

Pelvic Belt Effects on Health Outcomes and Functional Parameters of Patients with Sacroiliac Joint Pain

Abstract: IntroductionThe sacroiliac joint (SIJ) is a common source of low back pain. However, clinical and functional signs and symptoms correlating with SIJ pain are widely unknown. Pelvic belts are routinely applied to treat SIJ pain but without sound evidence of their pain-relieving effects. This case-control study compares clinical and functional data of SIJ patients and healthy control subjects and evaluates belt effects on SIJ pain.Methods17 SIJ patients and 17 healthy controls were included in this prospective s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 73 publications
2
30
0
Order By: Relevance
“…A number of experimental studies have postulated that orthoses may relieve pelvic ligaments 7 , 30 , 31 or decrease laxity of the SIJ, defined as an unphysiologic excessive movement within the joint 7 , 14 , 23 , 26 . These findings have been correlated to clinical findings on beneficial outcomes of orthosis applications 27 29 . However, to date, no study has shown how specifically SIJ kinematics become altered under orthosis application, and if the changes induced by orthoses are different in the healthy condition compared to the condition with insufficient ligaments.…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…A number of experimental studies have postulated that orthoses may relieve pelvic ligaments 7 , 30 , 31 or decrease laxity of the SIJ, defined as an unphysiologic excessive movement within the joint 7 , 14 , 23 , 26 . These findings have been correlated to clinical findings on beneficial outcomes of orthosis applications 27 29 . However, to date, no study has shown how specifically SIJ kinematics become altered under orthosis application, and if the changes induced by orthoses are different in the healthy condition compared to the condition with insufficient ligaments.…”
Section: Introductionmentioning
confidence: 77%
“…An established non-surgical approach to treat the painful SIJ is to apply pelvic orthoses 14 , 25 29 . A number of experimental studies have postulated that orthoses may relieve pelvic ligaments 7 , 30 , 31 or decrease laxity of the SIJ, defined as an unphysiologic excessive movement within the joint 7 , 14 , 23 , 26 .…”
Section: Introductionmentioning
confidence: 99%
“…However, since there is no single pain provocation test for SIJP, those who find relief using the belts may not have positive compression tests. Additionally, the belt may provide much wider dispersion of compression and therefore less localized compressive stress Hammer et al (2015) tested the use of pelvic belts on MRI confirmed non-inflammatory SIJP populations with age matched controls and saw improvements in pain scores after six weeks that were comparable to surgical fusion treatment. Additionally, rectus femoris muscle activity was decreased with moderate application and there were visible improvements in cadence and gait velocity (Hammer et al, 2015).…”
Section: Conservative Treatmentsmentioning
confidence: 86%
“…Additionally, the belt may provide much wider dispersion of compression and therefore less localized compressive stress Hammer et al (2015) tested the use of pelvic belts on MRI confirmed non-inflammatory SIJP populations with age matched controls and saw improvements in pain scores after six weeks that were comparable to surgical fusion treatment. Additionally, rectus femoris muscle activity was decreased with moderate application and there were visible improvements in cadence and gait velocity (Hammer et al, 2015). This decrease in rectus femoris muscle activity opposes results mentioned prior where manipulation caused an increase in activity (Barbosa et al, 2013).…”
Section: Conservative Treatmentsmentioning
confidence: 86%
See 1 more Smart Citation